2006
DOI: 10.1128/mcb.00941-06
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Induces Fibroblast Growth Factor 9 via EP3-Dependent Protein Kinase Cδ and Elk-1 Signaling

Abstract: Fibroblast growth factor 9 (FGF-9) is a potent mitogen that controls the proper development of many tissues and organs. In contrast, aberrant expression of FGF-9 also results in the evolution of many human diseases, such as cancers and endometriosis. Despite its vital function being reported, the cellular and molecular mechanisms responsible for the regulation of FGF-9 expression are mostly unknown. We report here that prostaglandin E 2 (PGE 2 ) induces expression of FGF-9, which promotes endometriotic stromal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 50 publications
1
45
0
Order By: Relevance
“…PGE 2 autoregulates COX-2 promoter activation and gene expression. Since KSHV infection-induced PGE 2 can initiate multiple signaling cascades (JNK-1, ERK1/2, PKC, PI3K-AKT, HPK1, and Src), second messengers, including cAMP, calcium (Ca 2ϩ ), and reactive oxygen species, in an autocrine/ paracrine manner by binding to its specific G-protein-coupled receptors (EP receptors) (3,4,6,16,18,27,32,33,35,37,38,46,52,73,77), we tested the role of exogenous PGE 2 in COX-2 promoter and COX-2 gene expression ( Fig. 2A and B).…”
Section: Resultsmentioning
confidence: 99%
“…PGE 2 autoregulates COX-2 promoter activation and gene expression. Since KSHV infection-induced PGE 2 can initiate multiple signaling cascades (JNK-1, ERK1/2, PKC, PI3K-AKT, HPK1, and Src), second messengers, including cAMP, calcium (Ca 2ϩ ), and reactive oxygen species, in an autocrine/ paracrine manner by binding to its specific G-protein-coupled receptors (EP receptors) (3,4,6,16,18,27,32,33,35,37,38,46,52,73,77), we tested the role of exogenous PGE 2 in COX-2 promoter and COX-2 gene expression ( Fig. 2A and B).…”
Section: Resultsmentioning
confidence: 99%
“…Further, nNOSderived nitric oxide contributes to ROS generation by interacting with the superoxide radical to produce peroxynitrite (Beckman et al, 1990), and to L-glutamate release (McNaught and Brown, 1998;Bal-Price et al, 2002). The involvement of the ERK1/2 pathway in PGE 2 -EP3 receptor-mediated signaling in other models (Chuang et al, 2006;Nicola et al, 2008) presented a rationale for investigating this pathway in the current study. Consistent with our hypothesis, intra-RVLM PGE 2 increased local ERK1/2 and nNOS phosphorylation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Equally important, there are no studies on a potential BP role for PGE 2 -EP3 receptor signaling in the RVLM, a major brain stem cardiovascular regulatory area. We reasoned that, if PGE 2 -evoked increases in NOX activity , c-Fos expression (Lacroix et al, 1996;Zhang et al, 2011), and ERK1/2 pathway activation (Chuang et al, 2006) occur in the RVLM, they may uncover a new role for RVLM PGE 2 , because triggering these molecular mechanisms in the RVLM causes sympathoexcitation and BP increase Minson et al, 1994;Ibrahim and Abdel-Rahman, 2012;Chen et al, 2013). Therefore, we used a multilevel experimental approach to investigate these novel and interrelated possibilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same study by Wing and coworkers, it was observed that not only FGF-9 is regulated by E 2, but also, FGF receptors 2IIIc and 3IIIc. More recently, a study revealed that PGE 2 , acting through its receptor EP3 induces the expression of FGF-9 in a dose dependent manner in endometriotic cells in vitro (Chuang et al, 2006) (Figure 2). …”
Section: Regulation Of Aromatase Activation and Estrogen Production Bmentioning
confidence: 99%